If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5x+40=6x-10
We simplify the equation to the form, which is simple to understand
-5x+40=6x-10
We move all terms containing x to the left and all other terms to the right.
-5x-6x=-10-40
We simplify left and right side of the equation.
-11x=-50
We divide both sides of the equation by -11 to get x.
x=4.5454545454545
| -21=6x-5-4x | | 23=b-15 | | (5/6)x-(2/3)=x | | (Y-3)(y^2+4)= | | -2.6-0.49=-1.79 | | 5(-3x+3)=4x-4 | | 10y+4x=10 | | y=-x^2+10x-28 | | 2/3x=3+1/2x | | x/2=8x-14/x | | -a=6 | | 6x+1+7x=-116 | | 4x+10y=12 | | 1.125(4-.5x)=3(.25x+2.5) | | 9x-4=4(x-1)-5+4 | | x-(x*.25)=7559.71 | | -5=-8y | | X-9y=-9 | | 7x+56=2x+70 | | 13=21-2x | | 0=-16t^2+88t-88 | | 7(x+2)=4+5x | | 59=28.10+0.15m | | r/r^-6r^-6 | | 2x^2=7-9x | | 32y+5y=10y | | -3x*7=18 | | 5+3(7-7x)=-8x+26 | | f(5)=8x-3 | | X/-9=54 | | 96=-16t^2+8t+96 | | -5x+7y-2=0 |